2015
DOI: 10.1007/s00125-015-3589-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased metabolic risk in adolescent offspring of mothers with type 1 diabetes: the EPICOM study

Abstract: Aims/hypothesis We aimed to investigate metabolic risk factors, insulin sensitivity and insulin secretion in adolescent offspring of mothers with type 1 diabetes compared with offspring of non-diabetic mothers. Methods During 1993-1999, pregnancies of women with type 1 diabetes in Denmark were prospectively reported to a central registry in the Danish Diabetes Association. Data included information on maternal demography, diabetes status and pregnancy outcome. We invited 746 eligible children from this cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 37 publications
3
79
4
Order By: Relevance
“…EPICOM (EPIgenetic, genetic and environmental effects on COgnitive and Metabolic functions in offspring of mothers with type 1 diabetes) is a Danish prospective nationwide follow-up study focusing on the long-term effects of intrauterine hyperglycemia (9). During 1993-1999 all pregnant women with type 1 diabetes in Denmark were prospectively reported to a central register in the Danish Diabetes Association (n = 1,215) (1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…EPICOM (EPIgenetic, genetic and environmental effects on COgnitive and Metabolic functions in offspring of mothers with type 1 diabetes) is a Danish prospective nationwide follow-up study focusing on the long-term effects of intrauterine hyperglycemia (9). During 1993-1999 all pregnant women with type 1 diabetes in Denmark were prospectively reported to a central register in the Danish Diabetes Association (n = 1,215) (1).…”
Section: Methodsmentioning
confidence: 99%
“…The cognitive tests were completed by 277 (37.1%) exposed and 301 (15.7%) unexposed offspring. Details about the inclusion process and follow-up have recently been published (9).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental history of type 2 diabetes and obesity consistently increase the risk of both disorders among offspring (Lyssenko et al 2008;Reilly et al 2005). Vlachová et al (2015) investigated metabolic risk-factors, prevalence of metabolic syndrome (MetS), and prediabetes in a Danish sample of adolescents with diabetic (type 1) mothers compared to a control group of adolescents of non-diabetic mothers. They reported that adolescents of diabetic mothers had a higher frequency of metabolic riskfactors, decreased insulin sensitivity, insufficient insulin secretion and a higher prevalence prediabetes compared to controls.…”
mentioning
confidence: 99%